2012
DOI: 10.1002/joc.3641
|View full text |Cite
|
Sign up to set email alerts
|

Canadian RCM projected changes to high flows for Québec watersheds using regional frequency analysis

Abstract: Information related to changes in streamflow characteristics is important in the management and future planning of various water resources-related projects in the context of a changing climate. In this study, projected changes to selected return levels of high flows for 21 watersheds, located mainly in the Québec province of Canada, are assessed following regional frequency analysis (RFA). This assessment is based on a ten-member ensemble of Canadian regional climate model (CRCM) transient climate change simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Approaches to converting coarsescale GCM simulations to project changes to peak flows and low flows vary. Some examples include direct downscaling of streamflow extremes by sparse Bayesian learning and multiple linear regression (Joshi et al, 2013), weather generators combined with hydrologic models (Cunderlik and Simonovic, 2007), regional frequency analysis of regional climate model (RCM) projections (Clavet-Gaumont et al, 2013), and, most commonly, statistical downscaling of GCM or RCM projections run through a physically based hydrologic model (Elsner et al, 2010a;Maurer et al, 2010;Shrestha et al, 2012;Bürger et al, 2011). The uncertainty in hydrologic projections from GCMs is greater than that from emissions scenarios or model parameterizations (Bennett et al, 2012;Prudhomme and Davies, 2008) and all GCMs represent the climate imperfectly in different ways (Gleckler et al, 2008;Knutti et al, 2008); therefore, to fully characterize the uncertainty in projected hydrological extremes, an ensemble of GCMs is required.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to converting coarsescale GCM simulations to project changes to peak flows and low flows vary. Some examples include direct downscaling of streamflow extremes by sparse Bayesian learning and multiple linear regression (Joshi et al, 2013), weather generators combined with hydrologic models (Cunderlik and Simonovic, 2007), regional frequency analysis of regional climate model (RCM) projections (Clavet-Gaumont et al, 2013), and, most commonly, statistical downscaling of GCM or RCM projections run through a physically based hydrologic model (Elsner et al, 2010a;Maurer et al, 2010;Shrestha et al, 2012;Bürger et al, 2011). The uncertainty in hydrologic projections from GCMs is greater than that from emissions scenarios or model parameterizations (Bennett et al, 2012;Prudhomme and Davies, 2008) and all GCMs represent the climate imperfectly in different ways (Gleckler et al, 2008;Knutti et al, 2008); therefore, to fully characterize the uncertainty in projected hydrological extremes, an ensemble of GCMs is required.…”
Section: Introductionmentioning
confidence: 99%
“…As for precipitation, the global average is projected to increase with increasing water holding capacity of the atmosphere in a warmer climate (Meehl et al 2007). For North America, Christensen et al (2007) reported projected decreases in future snow season length and snow depth, but increases in future precipitation in winter and spring for southern Canada. Increase in temperature and precipitation can significantly affect flood dynamics in Canadian river basins where high flows are primarily generated due to spring snowmelt (Mareuil et al 2007).…”
mentioning
confidence: 99%
“…Based on projections from 21 global climate models that participated in the AR4 (IPCC 2007), Christensen et al (2007) predicted that the annual mean temperature will increase by 3.6°C (with a range of 2.3-5.6°C) and precipitation by 7 % (with a range of -3 to 15 %), over eastern North America including middle and southern parts of Québec, for the 2080-2099 period with respect to the 1980-1999 period; these results consider the IPCC's (2001) Special Report on Emissions Scenarios (SRES) AlB scenario. The largest increase in mean temperature (3.8°C) and precipitation (11 %) is expected in winter, while the smallest increase in mean temperature (3.3°C) and precipitation (1 %) is expected in summer.…”
mentioning
confidence: 99%
“…The approach of RFA is to use the attainable data from gauged sites within a homogeneous region, to compute quantiles of several return periods in ungauged sites [1]- [3]. A regional approach to frequency analysis in poorly gauged areas makes possible a significant reduction of uncertainty associated with the assessment of hydrological events with a high return period [2], [4]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…The most important step in the RFA procedure is the selection/delineation of homogeneous regions [4], in other words, the process of gathering the selected stations-which have enough record length and other suitable propertiesinto groups that obey the hypothesis of statistical homogeneity. Whenever the grouped stations fulfill the assumption of statistical homogeneity, then RFA will take advantage of all the available information and will make reliable assessments of extreme quantiles using the fitted regional pdf [7], [8].…”
Section: Introductionmentioning
confidence: 99%